Borrow-To-Use Agreement and its Legal Consequences in Case of Damages on the Object of Agreement (Faculty of Law, Universitas Negeri Semarang, 2020)
The performance of a borrow-to-use agreement can only be enjoyed by one party while the other party will not obtain anything from the borrower’s party. The willingness to help or to lend the other party is probably is based on an agreement, volunteerism, solidarity, or is because of the object owner’s social sense. The regulation is already available in the Civil Codes. However, the question is whether the provisions in the Civil Codes regarding to borrow-to-use agreement are still relevant in the present situations and to the more complex society. The risks will rise along with the making of the agreement. Therefore, it is necessary that there is a sound mechanism to regulate and resolve problems regarding the emerging risks in the borrow-to-use agreement. The objectives of this study are to analyze provisions regarding a borrow-to-use agreement regulated by the Civil Codes and the legal consequences in the occurrence of the damage of the object of a borrow-to-use agreement in the perspective of the Civil Codes and to resolve risks occurring in the agreement. The study makes use of a normative juridical approach method by applying regulation approach. The data used are secondary data which come from the primary, secondary, tertiary materials. The object of the borrow-to-use agreement which is conducted by the society varies from movable to immovable objects. The most frequently used objects for a borrow-to-use agreement by the society are vehicles like cars, motorcycles, trucks, etc. The immovable objects which are frequently used include: houses, land, buildings, etc. In Indonesia, a borrow-to-use agreement is a common practice making use of various objects as its collaterals.